2018
DOI: 10.1016/j.comgeo.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Modem illumination of monotone polygons

Abstract: We study a generalization of the classical problem of the illumination of polygons. Instead of modeling a light source we model a wireless device whose radio signal can penetrate a given number k of walls. We call these objects k-modems and study the minimum number of k-modems sufficient and sometimes necessary to illuminate monotone and monotone orthogonal polygons. We show that every monotone polygon with n vertices can be illuminated with n−2 2k+3 k-modems. In addition, we exhibit examples of monotone polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In the case of orthogonal polygons, the bound becomes n 4 , as shown by Kahn et al [13]. For k-transmitters, Aichholzer et al [1] showed n 2k k-transmitters are always sufficient and n 2k+4 k-transmitters are sometimes necessary to cover a monotone n-gon 1 ; for monotone orthogonal polygons they gave a tight bound of n−2 2k+4 k-transmitters, for k even and k = 1. Aichholzer et al [2] improved the bounds on monotone polygons to a tight value of n−2 2k+3 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the case of orthogonal polygons, the bound becomes n 4 , as shown by Kahn et al [13]. For k-transmitters, Aichholzer et al [1] showed n 2k k-transmitters are always sufficient and n 2k+4 k-transmitters are sometimes necessary to cover a monotone n-gon 1 ; for monotone orthogonal polygons they gave a tight bound of n−2 2k+4 k-transmitters, for k even and k = 1. Aichholzer et al [2] improved the bounds on monotone polygons to a tight value of n−2 2k+3 .…”
Section: Introductionmentioning
confidence: 93%
“…Aichholzer et al [1] first formalized this problem by considering k-modems (k-transmitters), devices whose wireless signal can pass through at most k walls. Since 2010, little progress has been made on the problem of k-transmitters, or even the problem of 2-transmitters, despite reaching a wide audience as the topic of a computational geometry column by Joseph O'Rourke [18] in the SIGACT News in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, this variant of visibility has been explored more widely due to its relevance in wireless networks. In particular, it models the coverage areas of wireless devices whose radio signals can penetrate up to k walls [2,14]. This makes the problem particularly interesting for the limited workspace model, since these wireless devices are typically equipped with only a small amount of memory for computational tasks and may need to determine their coverage region using the few resources at their disposal.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that our ideas are also applicable for this notion and lead to an improvement of their result. 2 Related work. The optimal classic algorithm for computing the 0-visibility region needs O(n) time and O(n) space [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation